2023
DOI: 10.3390/cancers15072186
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Tetraspanin CD81 with Monoclonal Antibodies and Small Molecules to Combat Cancers and Viral Diseases

Abstract: Tetraspanin CD81 plays major roles in cell-cell interactions and the regulation of cellular trafficking. This cholesterol-embarking transmembrane protein is a co-receptor for several viruses, including HCV, HIV-1 and Chikungunya virus, which exploits the large extracellular loop EC2 for cell entry. CD81 is also an anticancer target implicated in cancer cell proliferation and mobility, and in tumor metastasis. CD81 signaling contributes to the development of solid tumors (notably colorectal, liver and gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 176 publications
(197 reference statements)
0
2
0
Order By: Relevance
“…In contrast, mAbs originate from the same B cell in a host animal, and it recognizes only one binding epitope or binding site on a protein , (Figure B). Previous reports suggest that mAbs target the open EC2 loop in CD81 . It has been shown that the EC2 loop in CD81 possesses sites that are crucial for recognition and cell interaction whereas the EC1 loop plays a less important role .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mAbs originate from the same B cell in a host animal, and it recognizes only one binding epitope or binding site on a protein , (Figure B). Previous reports suggest that mAbs target the open EC2 loop in CD81 . It has been shown that the EC2 loop in CD81 possesses sites that are crucial for recognition and cell interaction whereas the EC1 loop plays a less important role .…”
Section: Resultsmentioning
confidence: 99%
“…The next step in the functional analysis of E1E2 heterodimers was the study of their affinity to the recombinant large extracellular loop (LEL) of the human CD81 receptor fused to Glutathione S-transferase (GST). Tetraspanin CD81 is one of the main HCV entry receptors and a key player in the HCV lifecycle [ 19 ]. In this experiment, ELISA plates were coated with recombinant purified GST-CD81-LEL and incubated with the lysates of cells expressing E1E2 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible and even probable that PPV and other yet to be uncovered novel and ancient viruses emerging from permafrost thaw may also manifest affinities for CD71 receptor and for CD81 co-receptor. It follows that, whereas there is no anti-CD81 compound in clinical development at present, the current knowledge-base about the role of CD71 and CD81 in viral infections and immunopathology warrants more substantial considerations as a drug target [ 37 ].…”
Section: Discussionmentioning
confidence: 99%